Automatic Mist Sprayer for Oyster Mushroom Cultivation Using Thingspeak IoT Platform and R Analytical Tool - Julianti Habibuddin; Taufik Muchtar; Muhammad Fadli Azis; Muh. Rivaldi Sasmita (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
In mushroom greenhouses at IKM Simbang Maros, watering is currently done manually using a hose and scheduled twice daily, without considering the optimal temperature and humidity for mushroom growth. This study aims to develop an automatic watering system for oyster mushroom cultivation using a DHT22 sensor to monitor temperature and humidity. The system is equipped with a NodeMCU ESP32 microcontroller and a mist sprayer, triggered by a relay to activate the water pump. An IoT platform using Thingspeak allows farmers to monitor temperature and humidity data in real-time on their smartphones. In a real case study, the device effectively maintained optimal humidity levels for mushroom growth, with the pump activating when humidity was below 85%. Data from 10 observations showed that the pump was active for 7 times. Data processing using R Studio showed the system's ability to stabilize humidity levels. The proposed system could help farmers optimize mushroom growth and reduce the labor required for manual watering.